A recombinant TGF-β1 vaccine ameliorates diabetic nephropathy in OLETF rats. (September 2016) - Zhang, Haojun; Wang, Hua; Yan, Meihua; Zhao, Tingting; Lu, Xiaoguang; Zhu, Bin; Gong, Yuewen; Li, Ping
Aim: The aim of this study was to investigate the potential of a recombinant vaccine encoding TGF-β1 in OLETF rats with diabetic nephropathy (DN).Methods: OLETF rats were treated with vehicle or TGF-β1 vaccine. LETO rats were used as normal controls. At 42 weeks after immunization with vaccine, samples from blood, urine and kidney were collected for biochemical, histologic, immunohistochemical and molecular analyses.Results: OLETF rats treated with the vaccine reduced blood glucose levels, improved renal pathological changes, and inhibited overexpression of TGF-β1 and p-Smad3, as well as MCP-1, TNF-α and IL-1β.Conclusion: TGF-β1 vaccine attenuated diabetic nephropathy in OLETF rats through reduction of inflammation, improvement of kidney fibrosis and partial correction of glucose metabolism.